Kerjasama Internasional Dalam Upaya Pemberantasan â€˜Illicit Arms Traffickingâ€™ di Kawasan Asia Tenggara - Syahmin Ak; Fidelia Fidelia (Universitas Sriwijaya, 2018)
Advanted in science and technology in this globalization era have a profound influence on every humanâ€™s activities in this world. Dispite its benefits, globalization has its negative im pacts, like as dependency of human on technology, until led to a progressively increasing number of transnational crime. Based on the results of this research, we know that ASEAN as a regional international organization, have not been able to maintain the security of this area, and also itâ€™s because strategical policy is not comprehensive, because some crimes donâ€™t have any legal instruments that bind every ASEAN states. One of the crimes that have not been regulated in ASEAN is â€œIllicit Arms Traffickingâ€. Borrowing the definition used by the United Nations, illicit trafficking is the movement of weapons that is â€œcontrary to the laws of States and/or international law.â€ This phenomenon is of growing concern because it has the potential to undercut government efforts at establishing stability and order. Governments in Southeast Asia are worried about the growing illicit trade in small arms because a number of factors have allowed it to flourish steadily such as inadequate controls against illicit weapons production, exports and imports at the national level due to poorly trained and/or corrupt officials, financial and technological difficulties in implementing effective controls, lack of coordination and cooperation among regional states in monitoring the circulation and supply of weapons from within and outside of the region; and, non-existence of international or regional agreements on controlling the small arms trade (licit and illicit). Other obstacles that the breadth of water areas in Southeast Asia that so complicate ASEAN to kept an eye on any potential occurrence of transnational crime, including Illicit arms trafficking